ANALYSIS OF FACTORS AFFECTING THE WORK PRODUCTIVITY OF MSME ACTORS: A CASE STUDY OF HUMAN RESOURCES AND COMPETENCY DEVELOPMENT IN PEMATANG SERAI VILLAGE - Yanti, Eli Delvi; Macia Sari, Maya; Ardian, Noni; Hasibuan, Ratna Sari (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2024)
The purpose of this study is to determine and analyze the effect of Human Resource Development and Competence on the Work Productivity of MSME Actors in Pematang Serai Village, Langkat Regency. The specific target in this study is how to increase the work productivity of MSME business actors produced by business actors in Pematang Serai Kabaputen Langkat village so that it can be in demand by the wider community. The hypothesis in this study is to see the influence of competence and human resource development on the work productivity of MSME business actors. Themethod that will be used in this study is a quantitative method where the quantitative method in this study is related to data that describes the condition of the village community, especially MSME business actors in Pematang Serai Village, Langkat Regency can make good changes and product development significantly in order to increase income. The data analysis used was multiple linear regression analysis with statistical testing using SPSS v. 25.. The results showed that partially and simultaneously the variables of Human Resources and Competency Development had a positive and significant effect on the Work Productivity of MSME Actors in Pematang Serai Village.